2018
DOI: 10.2169/internalmedicine.0438-17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Eplerenone on the Glomerular Filtration Rate (GFR) in Primary Aldosteronism: Sequential Changes in the GFR During Preoperative Eplerenone Treatment to Subsequent Adrenalectomy

Abstract: Objective Eplerenone (EPL) is a mineralo-corticoid receptor antagonist that is highly selective and has few side effects. This study was conducted to examine whether or not EPL treatment was able to reverse glomerular hyperfiltration, as an indicator of aldosterone renal action, in primary aldosteronism (PA) patients. Methods Changes in the estimated glomerular filtration rate (ΔGFR) were examined in 102 PA patients with EPL treatment. Furthermore, the sequential ΔGFR in 40 patients initially treated with EPL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
9
2
1
Order By: Relevance
“…In patients with PA, renal glomerular hyperfiltration is present due to an excess of aldosterone, which causes elevation of eGFR. These elevations appear to be reduced by treatment with an MR blocker due to improved glomerular hypertension [ 36 , 37 ]. In our study, the extent of reductions in eGFR during treatment of PA with esaxerenone was similar to that seen with other MR blockers, indicating that correction of hyperfiltration probably contributed to the observed reduction in eGFR, which may indicate recovery of the tubuloglomerular feedback damaged by hyperaldosteronism [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with PA, renal glomerular hyperfiltration is present due to an excess of aldosterone, which causes elevation of eGFR. These elevations appear to be reduced by treatment with an MR blocker due to improved glomerular hypertension [ 36 , 37 ]. In our study, the extent of reductions in eGFR during treatment of PA with esaxerenone was similar to that seen with other MR blockers, indicating that correction of hyperfiltration probably contributed to the observed reduction in eGFR, which may indicate recovery of the tubuloglomerular feedback damaged by hyperaldosteronism [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…have noted that PA patients experienced a reduction in eGFR after taking a high-dose MR antagonist (which reflects improvement of glomerular hyperfiltration after treatment), but 82% of them experienced a further reduction in eGFR after surgical adrenalectomy. 33 This suggests that even a high-dose MR antagonist treatment may not adequately suppress MR activation within the kidneys, and that further improvement in glomerular hyperfiltration 33 may be possible via surgery. Hundemer et al.…”
Section: Discussionmentioning
confidence: 99%
“…Nakano et al have noted that PA patients experienced a reduction in eGFR after taking a high-dose MR antagonist (which reflects improvement of glomerular hyperfiltration after treatment), but 82% of them experienced a further reduction in eGFR after surgical adrenalectomy. 33 This suggests that even a high-dose MR antagonist treatment may not adequately suppress MR activation within the kidneys, and that further improvement in glomerular hyperfiltration 33 may be possible via surgery. Hundemer et al reported that surgical treatment was associated with a lower risk of kidney dysfunction compared to MR antagonist treatment among patients with PA. 8,9 In the current study, reduction in eGFR after treatment was greater in the surgical treatment group than among those in the MR antagonist treatment group.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…A series of clinical studies have shown that renal hemodynamic alteration due to hyperaldosteronism results in glomerular hyperfiltration, 5,6 which is a cause of chronic renal injury 7 . The glomerular filtration rate (GFR) in PA rapidly decreases after the removal of aldosterone excess by ADX 5,8–10 or the blockade of aldosterone action by MRA 11 . To prevent renal injury in the long term, complete removal of glomerular hyperfiltration by ADX or a sufficient dose of MRA is recommended for patients with PA 11 .…”
Section: Introductionmentioning
confidence: 99%